2019
DOI: 10.1007/s13197-019-04088-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of spray drying parameters and carrier material on the physico-chemical properties and quality of chokeberry juice powder

Abstract: Chokeberry juice is used in the food industry because of its antioxidant activity as well as anti-diabetes, anti-mutagenic, bacteriostatic, anti-inflammatory and antivirus properties. However in a liquid form its active ingredients can be unstable, so conversion into powder form is required. To improve the quality of the final product and extend information about the properties of chokeberry powder the aim of the study was to examine the relationship of inlet air temperature (160°C, 200°C) and carrier type mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 30 publications
6
27
0
Order By: Relevance
“…The Dx carrier resulted in fewer deformations and shrinkages on the surface of particles than the MDx carrier. Other authors also observed similar images of the microstructure of dried fruit juice particles on maltodextrin carriers [32,36,[43][44][45].…”
Section: Bulk Density Flowability and Moisture Contentsupporting
confidence: 58%
See 1 more Smart Citation
“…The Dx carrier resulted in fewer deformations and shrinkages on the surface of particles than the MDx carrier. Other authors also observed similar images of the microstructure of dried fruit juice particles on maltodextrin carriers [32,36,[43][44][45].…”
Section: Bulk Density Flowability and Moisture Contentsupporting
confidence: 58%
“…The changes were caused by an increase in the energy delivered to the sprayed juice droplets and an increase in the drying rate, i.e., a higher drying rate reduced the shrinkage of particles [35]. Gawałek et al [32], Bednarska and Janiszewska-Turak [36] also observed this trend in chokeberry juice dried on a maltodextrin carrier (MDx). Other authors also noted this dependency when drying other fruit juices: acai juice [37], jamun fruit juice [38], guava juice [39], tamarind pulp [40].…”
Section: Particle Sizementioning
confidence: 99%
“…No correlation between the content of red betalain pigment and red coefficient a* was observed (red colorant = 17.5845 + 0.2461* a*; r = 0.2792; P = 0.1766), but correlation for coefficient b* and yellow colourant was stated (yellow colourant = À52.1887 + 0.7704* b*; r = 0.6251; P = 0.0011). It is in contrast with research made for non-fermented chokeberry juice (Bednarska & Janiszewska-Turak, 2020), and for nonfermented beetroot juice, colourants were encapsulated by Azeredo et al (2007) and anthocyanin pigments were obtained by Jim enez-Aguilar et al (2011).…”
Section: Colour Of Fermented Beetroot Juice Microparticlesmentioning
confidence: 70%
“…The extracts were prepared according to methodology presented by Bednarska & Janiszewska-Turak (2020) and Nowacka et al (2014). Water extracts of spraydried powders were prepared for measurement: for this purpose, 0.3 g of material (AE0.0001 g precision) was weighed in beaker, and then, 30 mL of distilled water was added.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…Aronia contains also quercetin glycosides, primarily quercetin-3-glucoside, and phenolic acids, predominantly chlorogenic acid and neochlorogenic acid. It was proven that aronia fruits and extracts exhibit strong antioxidative potential in vitro [ 17 , 18 , 19 , 20 , 21 ]. Studies conducted by Zheng and Wang [ 17 ] showed that extracts from black chokeberries possess significantly stronger antioxidant activity than extracts obtained from blueberries ( Vaccinium corymbosum L.), cranberries ( Vaccinium macrocarpon Aiton), and lingonberries ( Vaccinium vitis-idaea L.).…”
Section: Introductionmentioning
confidence: 99%